Using Verb Extension to Gauge Children’s Verb Meaning Construals: The Case of Chinese - Ma, Weiyi; Golinkoff, Roberta Michnick; Song, Lulu; Hirsh-Pasek, Kathy (Frontiers in Psychology, 2021)
Verb extension is a crucial gauge of the acquisition of verb meaning. In English, studies suggest that young children show conservative extension. An important test of whether early conservative extension is a general phenomenon or a function of the input language is made possible by Chinese, a language in which verbs are more frequent and acquired earlier. This study tested whether 3-year-old Chinese children extended a group of familiar verbs that specify various ways to carry objects. Shown videos that portrayed typical, mid-typical, or atypical carrying actions (as verified by Chinese adults), children were asked to judge whether they were examples of specific Chinese carry verbs. Children’s verb extensions were mostly limited to typical exemplars, suggesting that early conservative extension may be universal. Furthermore, extension breadth was related to the onset of verb production: verbs acquired earlier elicited more extension judgments than those acquired later.